“…and we’re all going down!” Underground ontologies in conflict in Tierra Amarilla - Ureta, Sebastian; Contreras, Andrés (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
On November 2013 a massive sinkhole appeared in a terrain near Tierra Amarilla, a small mining town in northern Chile. This event immediately raised the alarms of the local population, given the possible occurrence of new sinkholes directly in the inhabited area of the city. In order to deal with such fears, the local mining companies established a task force with representatives of the community, authorities and mining experts. At the center of this task force work was the difficult cohabitation between two contrasting ontologies about the local mining underground, one associating it with risks and ruination and the other with transparency and control. Using science and technology studies (STS) conceptual devices, on this paper the work done by this task force is analyzed as a process through which the first ontology was solely seen as an erroneous understanding of the second one, a “myth” emerging out the local population’s ignorance. Such framing end up producing a closure for the controversy that left untouched the neighbor’s original matters of concern, becoming more an example of a radical equivocation than a perfect application of corporate social responsibility, as it was presented afterwards.